Study of Gendered Language in Blogs: A Corpus-Based Analysis of Fixed Phrases - Muhammad Yousaf; Ijaz Ali Khan; Azhar Habib (Corporum, 2019)
The study explored fixed phrase fragments from the corpus of Pakistani blogs written by male and female bloggers in order to compare and contrast the language used by them. The fixed structures were analyzed and categorized with the help of the framework provided by BiberandConrad(1999) and later adapted by Yousaf (2019) for Pakistani context. The results proved that both male and female writers use fixed phrases and rely heavily on them. Similarly, the study revealed that male and female writers used different percentages of fixed phrases belonging to different categories. Male bloggers used the highest percentage of Prepositional Phrase Fragments which is actually in line with the international norms as many studies highlight a high percentage of ̳Prepositional Phrase Fragments‘ in different genres (see studies such as Hyland, 2008; Biber&Conrad,1999; Biber, Conrad, & Cortes, 2004). On the other hand, if we look at the highest percentage of fixed structures by female bloggers, Noun Phrase Fragments are on the top with 22.41% of the total which is the second highest category in the blogs by male bloggers, although the difference is not very high yet the highest percentage of these structures in blogs by female bloggers is making it highly noticeable. The second highest category by female bloggers is Anticipatory It, That/There/To Fragments which is 18.96%. This category shows the stance of the writers whether they want to put their viewpoint directly or they keep the actor in the background. In this sense, female bloggers are more unbiased and present their view without focusing on the actor rather, they foregrounding the act. Hence, it can be concluded that fixed phrases in blogs have variation because of the gender of the bloggers.